Implementation of School Principal’s Leadership Management in Strengthening Students’ Character (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2025)
This study aims to examine the implementation of school principal leadership management in strengthening students’ character, focusing on the four managerial functions of planning, organizing, actuating, and evaluating. Using a qualitative descriptive approach, the research was conducted at SD Negeri 53 Palembang with data collected through semi-structured interviews, non-participant observation, and document analysis involving the principal, teachers, students, and parents. The findings show that the principal’s leadership management effectively supports the development of students’ character through structured planning, distributed role organization, consistent role modeling, and systematic evaluation. Character values were reinforced through daily–weekly–monthly habituation routines, supported by collaborative involvement between teachers, students, and parents. The study also reveals several contextual challenges—such as inconsistent discipline and limited parental reinforcement—which prompted the principal to apply adaptive strategies including revising morning routines, strengthening parent communication, and providing personalized mentoring. These adaptive mechanisms ensured continuous improvement and alignment between planned programs and actual student needs. This study contributes a practical and replicable leadership model demonstrating how managerial consistency, stakeholder collaboration, and ongoing evaluation synergistically foster sustainable character education in elementary schools.